2002
DOI: 10.1590/s0004-282x2002000100007
|View full text |Cite
|
Sign up to set email alerts
|

Terminal ileum submucous plexus: Study of the VIP-ergic neurons of diabetic rats treated with ascorbic acid

Abstract: -The aim of this study was to evaluate the effect of the ascorbic acid (AA) supplementation on the neurons that produce the vasoactive intestinal peptide (VIP) in the submucous plexus of the ileum of rat, four months after the induction of experimental diabetes mellitus with streptozotocin. Three groups of rats were used: C -control, D -diabetic, DA -diabetic receiving AA. We have measured the immunoreactivity and area of 80 cellular bodies of VIP-ergic neurons from each studied group. In the diabetic animals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 29 publications
6
32
0
1
Order By: Relevance
“…The metabolic abnormalities found (polyuria, polydipsia, polyphagia and weight loss) are consistent with the literature, in the case of diabetic animals (17,39) . When the potential for glycogen storage of the kidneys is exceeded, the high glucose level in blood promotes glucosuria.…”
Section: Discussionsupporting
confidence: 91%
“…The metabolic abnormalities found (polyuria, polydipsia, polyphagia and weight loss) are consistent with the literature, in the case of diabetic animals (17,39) . When the potential for glycogen storage of the kidneys is exceeded, the high glucose level in blood promotes glucosuria.…”
Section: Discussionsupporting
confidence: 91%
“…An increase (p<0.05) of the glycemia and blood glucose was observed in group D, confirming that these animals had the diabetic syndrome, similar to what was observed by Zanoni et al 15 . The ALC supplementation did not act immediately in the metabolic control of DM, as evidenced by the similar levels of blood glucose between groups D and DC.…”
Section: Discussionsupporting
confidence: 89%
“…The expressive increase of the area verified in groups D and DC could be related not only to the increment of the synthesis machinery but also to its accumulation and expression difficulties. We observed an increase in the immunoreactivity to VIP associated to an increase of the area, thus indicating that the accumulation of this substance within the neurons was similar to what was previously observed in VIP-ergic neurons of the terminal ileum of diabetic rats 15 . See et al 19 analyzed the submucous VIP neurons of the jejunum of rats after chemical denervation and verified that the area of these neurons increases once the myenteric and extrinsic pulse is removed from the jejunum.…”
Section: Groupsupporting
confidence: 88%
“…Zanoni et al (2003) when used the myosin-V technique for staining the total population of myenteric neurons, did not observe significant differences between the number of neurons when comparing the groups of diabetic animals and the ascorbic acid supplemented. On the other hand, Zanoni et al (2002) and Zanoni et al (2003) reported that the ascorbic acid supplementation was positive on the VIP-ergic submucous and nitrergic neurons (NADPHdiaphorase histochemistry technique) of the ileum of diabetic rats, respectively. The ascorbic acid supplementation is beneficial for diabetics since, according to Garg and Bansal (2000), it reduces the levels of lipidic and plasmatic peroxidation, regulates the plasmatic levels of vitamin C and increases the levels of vitamin E, besides increasing the glutathione peroxidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in the number of neurons demonstrates that the diabetes mellitus causes the death of these cells. Besides, alterations had also been observed in its morphology, in cases of chronic diabetes, in different intestinal segments (Romano et al, 1996;Zanoni et al, 1997;Hernandes et al, 2000;Fregonesi et al, 2001;Zanoni et al, 2002;Zanoni et al, 2003). The ascorbic acid is a substance that acts as antioxidant and also promotes the reduction on sorbitol plasmic concentration, inhibiting the aldose reductase (Vinson et al, 1989).…”
Section: Introductionmentioning
confidence: 99%